THE PERFORMANCE ANALYSIS OF HEALTH, SAFETY, ENVIRONMENT, AND ENERGY INTEGRATED MANAGEMENT SYSTEM (HSEE-IMS) USING FUZZY COGNITIVE MAPPING METHOD - Rasoul Yarahmadi (University of Kragujevac, 2021)
The performance assessment of strategic levels of an integrated management system (IMS) is critical to policy making phase of executive organizations. Because, the integrity of objectives and strategies in the overall system performance insures the integrity of activities and performance in the subsidiary departments and units. Unfortunately, this approach of assessment has been rarely focused. Here, the Fuzzy Cognitive Mapping-Relative Degree Analysis (FCM-RDA) technique was chosen to assess the performance trend of the health, safety, environment, and energy (HSEE)-IMS in a ministry during 2014-2019. There were 12 HSEE-IMS strategic sub-elements and 6 system sub-performances. The Gephi0.9.2 software was applied to simulate the FCM model. Accordingly, the sub-performance of policy and leadership was placed at the first priority. The development of HSEE management, and review (of policies and programs) were two HSEE-IMS sub-elements, categorized in the second priority. The results showed an ascending trend of the system performance during 2014-2018 and a descending trend during 2018-2019. It was found that the poor performance of HSEE-IMS sub-elements in the strategic and tactical levels resulted in the poor performance of system at the operational levels. There was found a strong relationship between the HSEE-IMS sub-elements and system sub-performances.